Effects of UV-B radiation on anatomical characteristics, phenolic compounds and gene expression of the phenylpropanoid pathway in highbush blueberry leaves - Inostroza-Blancheteau, Claudio (Plant physiology and biochemistry : PPB, 2014)
The effects of increased doses of UV-B radiation on anatomical, biochemical and molecular features of leaves of two highbush blueberry (Vaccinium corymbosum L. cv. Brigitta and Bluegold) genotypes were investigated. Plants were grown in a solid substrate and exposed to 0, 0.07, 0.12 and 0.19 Wm(-2) of biologically effective UV-B radiation for up to 72 h. Leaf thickness and the adaxial epidermis thickness fell more than 3-fold in both genotypes at the highest UV-B dose. Moreover, in Bluegold an evident disorganization in the different cell layers was observed at the highest UV-B radiation. A significant decrease in chlorophyll a/b after 6 h in Brigitta under the greater UV-B doses was observed. Anthocyanin and total phenolics were increased, especially at 0.19 Wm(-2), when compared to the control in both genotypes.Chlorogenic acid was the most abundant hydroxycinnamic acid in Brigitta, and was significantly higher (P ≤ 0.05) than in Bluegold leaves. Regarding the expression of phenylpropanoid genes, only the transcription factor VcMYBPA1 showed a significant and sustained induction at higher doses of UV-B radiation in both genotypes compared to the controls. Thus, the reduction of leaf thickness concomitant with a lower lipid peroxidation and rapid enhancement of secondary metabolites, accompanied by a stable induction of the VcMYBPA1 transcription factor suggest a better performance against UV-B radiation of the Brigitta genotype